VESICO-VAGINAL FISTULA: EXPERIENCE OF 11 YEARS - Taher, Taufik Rakhman; Zulfikar, Zulfikar; Wahyudi, Irfan; Rodjani, Arry (Indonesian Urological Association, 2013)
Objective: To evaluate the outcome of surgical repair in patients with vesico-vaginal fistula at Cipto Mangunkusumo Hospital. Material & Method: A retrospective study of 30 patients with vesico-vaginal fistula, who underwent surgical repair of the fistula at Urology Department Cipto Mangunkusumo Hospital between the period of 1998-2008, were reviewed. Patients were analyzed with regard to age, location of fistula, etiology, size of fistula, and surgical approach. The outcome of the surgery was analyzed. Results: This study included 30 patients who underwent surgery with age between 18-69 years old. The most common etiology was due to obstetrical trauma and hysterectomy. Bladder trigone was the most common location of fistulae (40%). During the surgery the transvesical (43%) approach was commonly used. However, the most excellent outcome was surgery by transvesical-transvaginal approach (100%). Success rate of fistula repair was 73%. Conclusion: This disease is a medically and psychosocially devastating condition for the patient. The diagnosis was easy but complicated in decision of treatment. Best results were observed by transvesical-transvaginal approach. Keywords: Vesico-vaginal fistulae, surgical approach, surgical outcome.